LA LUNGHEZZA DI PRIMA MATURITÀ QUALE RIFERIMENTO PER LA TAGLIA MINIMA DI CONSERVAZIONE NELLA GSA 16 - Biancardi, Sara (Biologia Marina Mediterranea, 2024)
The deep water rose shrimp, Parapenaeus longirostris (Lucas, 1846), DPS, the European hake, Merluccius merluccius (Linneus, 1758), HKE, the striped red mullet, Mullus surmuletus (Linneus, 1758), MUR, the red mullet, Mullus barbatus (Linneus, 1758), MUT, and the norway lobster, Nephrops norvegicus (Linneus, 1758), NEP, are the main target species of the Sicilian trawlers operating in the GSA 16. Given the state of exploitation of these stocks and their economic importance, the length at first maturity (L50) of the species is compared with their minimum conservation reference sizes (MCRS). The results show that, except for DPS, in all species the ratio L50/MCRS is >1 Results are discussed on light of the state of different stocks in the area.